No reef-associated gradient in the infaunal communities of Rapa Nui (Easter Island) – Are oceanic waves more important than reef predators?. (15th October 2018) - Gusmao, Joao B.; Lee, Matthew R.; MacDonald, Ian; Ory, Nicolas C.; Sellanes, Javier; Watling, Les; Thiel, Martin
Abstract: Reef-associated predators are thought to influence the distribution of invertebrates of surrounding sediment habitats. In this study, we analyzed the predation pressure and the distributional patterns of macro- and meiofaunal assemblages in soft sediments surrounding two coral reef sites at Rapa Nui (Easter Island), in the central South Pacific. We tested the hypothesis that reef-associated predators negatively affect sediment-dwelling invertebrates, causing macro- and meiofauna to be less abundant and diverse in soft sediments near the reefs. As expected, predation intensity was greater nearer the reef than farther away, but macro- and meiofaunal assemblages did not differ significantly with distance from the reef. Taxon richness of macro- and meiofaunal assemblages were similar irrespective of distance from the reef. Only meiofauna showed significant variation in total abundance with distance from the reef, but this trend was not consistent between the two study sites. No gradient in sediment texture was observed with distance from the reef. Underwater video recordings at one study site also revealed that local hydrodynamics cause frequent disturbance and resuspension of the upper sediment layers. Our results suggest that soft-sediment assemblages are constantly reshuffled by oceanic waves, thereby blurring the potential effects of predation on invertebrate assemblages closer to the reef.